2005
DOI: 10.1590/s0103-84782005000600016
|View full text |Cite
|
Sign up to set email alerts
|

A weight loss protocol and owners participation in the treatment of canine obesity

Abstract: The success of a weight loss program for pets depends on the owners collaboration. Their compliance is fundamental in establishing the correct food management. The objective of this study was to compare the effectiveness of a weight loss program in two groups of dogs, one maintained under experimental conditions and the other with their owners. The same hypocaloric food was used to feed all animals, the amount being restricted to 60% of the estimated maintenance energy requirement for a 15% reduction of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 13 publications
6
31
0
17
Order By: Relevance
“…Kienzle et al (1998) found owners of obese dogs more likely to believe exercise and balanced dog nutrition were less important than were owners of normal weight dogs. Carciofi et al (2005) cited factors such as lack of time to exercise the dog and the cost of specialized dog foods as barriers preventing compliance with weight loss treatments. Despite the possible existence of different beliefs between owners of normal weight and obese weight dogs, research has not investigated whether these beliefs are related to differences in feeding and exercise intentions and behaviors.…”
mentioning
confidence: 99%
“…Kienzle et al (1998) found owners of obese dogs more likely to believe exercise and balanced dog nutrition were less important than were owners of normal weight dogs. Carciofi et al (2005) cited factors such as lack of time to exercise the dog and the cost of specialized dog foods as barriers preventing compliance with weight loss treatments. Despite the possible existence of different beliefs between owners of normal weight and obese weight dogs, research has not investigated whether these beliefs are related to differences in feeding and exercise intentions and behaviors.…”
mentioning
confidence: 99%
“…However, methods that are successful under controlled laboratory conditions have the potential to be less effective in a real-world setting ( 9 ) . In particular, pet weight-loss and obesity prevention strategies are subject to a number of factors that influence compliance, including client perceptions of hunger ( 12 ) and the use of non-standard measurement systems ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Opções terapêuticas nutricionais têm sido investigadas para cães (Carciofi et al, 2005;Brunetto et al, 2008) e gatos (Vasconcellos et al, 2009) obesos. Importante preocupação com dieta restrita de energia, no entanto, é que esta cubra todas as necessidades de nutrientes essenciais, especialmente aminoácidos.…”
Section: Papel Da Nutrição Na Prevenção E Suporte De Afecçõesunclassified